PERFORMANCE OF MODIFIED HYBRID SOLAR DRYER ON THE DRYING PROCESS OF ROBUSTA CHERRY COFFEE - Evanila Silvia; Yuwana Yuwana; Bosman Sidebang (Jurnal Agroindustri, 2019)
Drying process is one of the most critical post-harvest stages because it can affect the quality of coffee beans. To overcome the obstacles that are often encountered in the drying process, many solar energy dryers have been developed with various ways of energy utilization and its characteristics, one of them is Modified Hybrid Solar Dryer. The purpose of this study was to test the performance of the furnace and heater distributor (temperature and humidity of the drying chamber) compared to the temperature and humidity outside the dryer when drying coffee cherries at 3 variations in the thickness of the sunbed; 5, 10 and 15 cm. Parameters of the performance of furnaces and heating distributors are: 1) the drying chamber temperature and the outside environment, 2) the relative humidity of the drying chamber and the outdoor, 3) the speed of the airflow in the drying chamber and 4) the drying time. Testing (experiments) carried out in 3 series, and the measurement results are averaged. Observations were made every 30 minutes from 9:00 am to 06:00 am for three days. Parameters of the quality of the effects of drying coffee beans: 1) the initial weight of the coffee beans, 2) the weight loss of the coffee cherries during drying; conducted moisture content of coffee cherries every hour from 09.00 am to 06.00 am. 3). The results obtained are the furnace and distributor of hybrid solar dryer heat able to increase air temperature is 19,25oC higher than the outside air temperature and reduce relative humidity 46,02% lower than the average relative humidity of the outside air with an average speed of airflow in the range of 0,42 – 0,50 m / s. Hybrid solar dryers can finish drying coffee fruits much faster in about 60 hours (15 cm thickness), 52 hours (10 cm thickness), and 36 hours (5 cm thickness) compared to sun dryingProses pengeringan merupakan salah satu tahapan pasca panen yang sangat kritis karena dapat mempengaruhi kualitas biji kopi. Untuk mengatasi kendala yang sering ditemui pada proses pengeringan,  banyak dikembangkan pengering berenergi surya dengan berbagai cara pemanfaatan energi dan karakteristiknya, salah satunya pengering surya Hybrid Modified. Tujuan dari penelitian ini adalah menguji kinerja tungku dan distributor pemanas (temperatur dan kelembaban ruang pengering) dibandingkan dengan temperatur dan kelembaban di luar pengering saat mengeringkan buah kopi pada 3 variasi ketebalan jemur yaitu 5, 10 dan 15 cm. Pengujian kinerja tungku dan distributor pemanas dilakukan dengan mengukur : 1) temperatur ruang pengering dan lingkungan luar,  2) kelembaban relatif ruang pengering dan lingkungan luar, 3) kecepatan aliran udara di ruang pengering dan 4) waktu pengeringan. Pengujian (percobaan) dilakukan 3 seri dan hasil pengukuran dirata-rata. Pengamatan dilakukan tiap 30 menit mulai pukul 9.00 sd 06.00 wib selama 3 hari. Pengamatan kualitas hasil pengeringan biji kopi dilakukan dengan mengukur : 1) berat awal buah kopi, 2) berat buah kopi selama pengeringan, dilakukan setiap jam dari pukul 09.00 sd 06.00 WIB. 3) kadar air biji kopi. Hasil yang diperoleh adalah tungku dan distributor panas pengering surya hybrid mampu meningkatkan temperatur udara adalah 19,25oC lebih tinggi dari temperatur udara luar dan menurunkan kelembaban relatif 46,02% lebih rendah dari kelembaban relatif rata-rata udara luar dengan kecepatan rata-rata aliran udara berkisar 0,42 – 0,50 m/s. Pengering surya hybrid dapat menyelesaikan pengeringan buah kopi jauh lebih cepat sekitar 60 jam (ketebalan jemur 15 cm), 52 jam (ketebalan jemur 10 cm) dan 36 jam (ketebalan jemur 5 cm) dibandingkan penjemuran biasa